Typologies of sport structures in writing and implementing European Projects: A two-step cluster analysis - Ionescu, Anca-Maria; Stănescu, Monica; Aivaz, Kamer-Ainur (Technium Social Sciences Journal, 2022)
In this paper we analyze information about the trends in sports structures in writing and implementing European funds, dividing them into three clusters, using SPSS Two-step Cluster method. When talking about sport structures and their relation with writing and implementing European projects in the field of sport, may not share all the same characteristics. This study aimed to identify typologies of sport structures who engage in writing and implementing European projects. The authors propose a method for a better understanding of the expectations of sports structures in the field of European funds and for managing future participants to European funds trainings effectively. About 433 sport structures completed an online questionnaire. Two-step cluster analysis identified three subgroups, based on projects with non-reimbursable funding that they have benefited from in the last 5 years, type of funding programs (external funds/state budget) and the presence of specialized internal human resources for writing and implementing projects inside their organisation. The largest group contains 222 respondents (53.4%), whose profile shows that they represent sport structures that have never beneficiated from European funds in the last past 5 years (100%), they are not considering hiring new human resources specialized in writing and implementing projects (100%) and don’t know a specific funding line / program (72.5%). The second group consists in 104 respondents (25%) – sport structures’ representatives that have beneficiated from European funds in the last past 5 years (99%), they are considering hiring new human resources specialized in writing and implementing projects (52.9%) and as a type of funds they are aware of the subsidies provided from the state budget. The third profile gathers 90 respondents, sport structures’ representatives that have not beneficiated from European funds in the last past 5 years (98.9%), but they are considering hiring new human resources specialized in writing and implementing projects (100%). Instead, this group doesn’t know the funding opportunities that the state or the European Commission provides for Romania. The benefit of the study is reinforcing the sport structures’ profits by managing their training in the field of European funds more effectively.